Near infrared spectrum testing method for charged submicron powder
Through the near-infrared spectroscopy test method combined with charge injection and spectral analysis, the problem of difficulty in accurately determining the relationship between charged submicron particles in the prior art is solved, and the stability and optimization of material properties are achieved.
Patent Information
- Application Number
- CN202411984389.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to accurately determine the affinity of charged submicron particles, resulting in unstable material performance and failing to meet the expected high standards.
The near-infrared spectral testing method of charged submicron powder is used to accurately determine the affinity of submicron particles through raw material pretreatment, charge injection, spectral measurement and analysis steps, combined with electrical and optical measurement methods, and the scattering enhancement effect of surface charge on submicron particles.
The precise affinity determination of charged submicron particles is achieved, the stability and optimization ability of material properties are improved, and the problem that the prior art cannot accurately judge the affinity of submicron particles is solved.
Smart Images

Figure CN119779929A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of submicron particle testing, in particular to a near infrared spectrum testing method for charged submicron powder. Background Art
[0002] The size of charged particles such as charged smoke, magnetic microspheres, and electrostatically atomized droplets has gradually extended to the mesoscopic and microscopic scales, which has put forward higher requirements for the accurate measurement of particles. Although efficient and non-destructive light scattering technology has gradually replaced traditional measurement methods and instruments for the measurement of micron-level particle concentration and particle size, it is still a great challenge to measure submicron and even ultramicron-scale particles. The reasons are mainly reflected in two aspects: 1) The smaller the particle diameter, the weaker the scattered light intensity, which increases the difficulty of measurement; 2) The scattering of submicron particles is easily disturbed by surface charge, which affects the measurement accuracy. The scattering enhancement effect can transform this "interference" and stably enhance the scattered light, providing a feasible solution for submicron particle measurement. However, research based on this effect has been in the theoretical exploration stage.
[0003] In the field of materials science, the affinity of submicron particles has a crucial impact on material performance. Due to the inability to accurately determine the affinity of charged particles, existing technologies can only perform relatively extensive tests during material synthesis and performance optimization. In the field of composite materials, when a product is composed of a variety of different submicron particle components, the quality of its performance is closely related to the "affinity" between the components. Previously, due to the inability to accurately determine the affinity of these submicron particles, the performance of the synthesized materials during the research and development process was unstable and could not meet the expected high standards. Summary of the invention
[0004] In view of the above-mentioned defects of the prior art, the present invention provides a near infrared spectroscopy test method for charged submicron powder, comprising the following steps:
[0005] S1, raw material pretreatment step, the submicron powder to be tested is dispersed and then dried;
[0006] S2, a charge injection step, placing the pretreated submicron powder in an electrostatic generator, setting relevant parameters, and injecting saturated charge into the submicron powder;
[0007] S3, a spectrum measurement step, placing the submicron powder injected with saturated charge on a test bench to obtain its spectrum;
[0008] S4, analysis step, preprocessing the spectral data, comparing and matching the preprocessed spectrum with a known submicron powder standard spectrum library, judging the material composition and chemical structure information of the sample by calculating the spectral similarity index, and determining its relationship with the standard sample and category affiliation.
[0009] Furthermore, the pre-processing step includes:
[0010] Dispersion treatment steps: add a small amount of anhydrous ethanol to the submicron powder and grind it to make the powder evenly dispersed to form a stable suspension;
[0011] Drying step: The suspension is dried in a vacuum drying oven until the ethanol is completely evaporated.
[0012] Furthermore, the relevant parameters include voltage, current and duration.
[0013] Furthermore, the spectral data preprocessing step includes:
[0014] The submicron powder is measured three times, and the spectral data of the three measurements are averaged;
[0015] The multivariate scatter correction method is used to remove the spectral baseline drift and scattering effects;
[0016] The spectra were smoothed using the Savitzky-Golay convolution smoothing algorithm.
[0017] Furthermore, the similarity index is a similarity coefficient or a Euclidean distance.
[0018] Furthermore, the particle size range is 0.1 to 1.0 μm.
[0019] Compared with the prior art, the present invention has the following technical effects:
[0020] The invention measures the particle size after surface charge injection into submicron particles, combines electrical methods with optical measurement methods, and applies the scattering enhancement effect of surface charge on submicron particles to the measurement of submicron powders, thus solving the problem in the prior art that the relationship of submicron particles cannot be accurately determined.
[0021] The technology provided by the present invention can accurately determine the affinity of charged submicron particles, so that material researchers can select suitable submicron particles for combination and optimization based on accurate affinity information, thereby effectively improving material performance and solving the problem that the existing technology cannot accurately determine the affinity of submicron particles.
[0022] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the principle of the present invention;
[0024] Figure 2It is a comparison result of the absorption peak intensity of the particles without charge injection and the particles with saturated charge at a charging voltage of 5 kV in a specific embodiment of the present invention;
[0025] Figure 3 It is a comparison result of the half-height width of the absorption peak of the particles without charge injection and the particles with saturated charge at a charging voltage of 5 kV in a specific embodiment of the present invention;
[0026] Figure 4 It is a comparison result of the absorption peak intensity between particles without charge injection, particles with saturated charge and a certain target particle in a specific embodiment of the present invention;
[0027] Figure 5 It is a comparison result of the half-width of absorption peaks between uncharged particles, saturated charged particles and a certain target particle in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0028] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.
[0029] Since the affinity of submicron particles cannot be accurately determined, the performance of the synthesized materials during the research and development process is unstable and cannot meet the expected high standards. In order to solve this problem, in a specific implementation, a near-infrared spectroscopy test method for charged submicron powder is provided. The principle is as follows: Figure 1 shown.
[0030] In this embodiment, the charged submicron powder is charged silica particles, and the particle size range is 0.1-1.0 μm. Before measuring, the following preparations are performed:
[0031] The experimental environment conditions of this embodiment are set as follows: the temperature of the laboratory is maintained at 20°C-25°C, the relative humidity is controlled at 40%-60%, and the instrument is placed on a stable laboratory table without obvious vibration, away from large motors, transformers and other equipment that may generate electromagnetic interference.
[0032] Instrument component inspection: Carefully check the key components of the near-infrared spectrometer, such as the light source, detector, optical fiber, etc., to ensure that there is no dust or stains attached, and that all components are tightly connected and not loose.
[0033] Preheating and parameter setting: Turn on the instrument power and preheat according to the instrument operation manual. The preheating time should be no less than 30 minutes to ensure the stability of the light source and detector. At the same time, set the wavelength range to 900-1700nm (this range is sensitive to the chemical structure and charge characteristics of submicron powders) in the instrument software, the number of scans to 32 times, the resolution to 8cm-1, the data acquisition interval to 2nm, and the integration time to 50ms.
[0034] The near infrared spectroscopy test method for charged submicron powders includes the following steps:
[0035] S1, raw material pretreatment step, dispersing the submicron powder to be tested and then drying it, specifically including:
[0036] S11, dispersion treatment step: the charged submicron powder sample is placed in an agate mortar, a small amount of anhydrous ethanol is added and then gently ground to evenly disperse the powder to form a stable suspension to prevent particle agglomeration and ensure that the measurement results can reflect the characteristics of a single particle. In this embodiment, the mass ratio of the charged submicron powder sample to anhydrous ethanol is about 1:10;
[0037] Drying step: Transfer the dispersed sample suspension to a glass petri dish, place it in a vacuum drying oven, and dry it for 2 hours at a temperature of 40°C and a vacuum degree of 0.08MPa until the ethanol is completely evaporated and the sample returns to a dry powder state.
[0038] S2, a charge injection step, placing the pretreated submicron powder in an electrostatic generator, setting relevant parameters, and injecting saturated charge into the submicron powder.
[0039] In this embodiment, a submicron powder sample with unstable charge after drying is placed in the discharge end of a negative polarity corona generator, and the sample is injected with charge until saturation by controlling relevant parameters such as voltage, current and charging time. In this embodiment, a DC high voltage power supply is used, and the voltage is set to 10 kV, the current is set to 1 mA, and the charging time is set to 60 seconds. In the specific application process, the setting of relevant parameters can be adjusted and optimized according to the properties of the sample and the required charge amount. In the process of charge injection, the safety of the operation process must be ensured to prevent electrostatic discharge from causing damage to personnel and equipment.
[0040] S3, a spectrum measurement step, placing the submicron powder injected with saturated charge on a test bench to obtain its spectrum;
[0041] In this embodiment, a submicron powder sample with a saturated charge is gently poured into a special quartz sample cell, and the sample surface is gently flattened with a flat quartz sheet so that the sample is evenly distributed in the light path with a thickness range of 2-3 mm to avoid the sample being too thick or too thin to affect the penetration and scattering of light.
[0042] Place the sample pool with the sample on the sample stage of the instrument, ensure that the sample pool is accurately positioned and well fixed, and start the measurement program. During the measurement process, closely observe the operating status of the instrument to ensure that the light source emits stably, the detector responds normally, and no abnormal alarm information appears.
[0043] Before measurement, the instrument needs to be calibrated, and the calibration process includes wavelength calibration and baseline calibration.
[0044] The wavelength calibration process includes: using a standard substance with a known wavelength (such as a polystyrene film), placing it in a sample cell, and performing a wavelength calibration operation according to the instrument calibration procedure, so that the deviation between the actual measurement wavelength of the instrument and the standard wavelength is controlled within ±0.5nm to ensure wavelength accuracy.
[0045] The baseline calibration process includes measuring an empty sample cell under the same conditions as the sample measurement and recording its spectral information as the baseline. The baseline correction function of the instrument software is used to perform real-time correction on the spectrum of subsequent sample measurements to eliminate the influence of instrument background noise and stray light and improve the signal-to-noise ratio of the spectrum.
[0046] S4, analysis step, preprocessing the spectral data, comparing and matching the preprocessed spectrum with a known submicron powder standard spectrum library, judging the material composition and chemical structure information of the sample by calculating the spectral similarity index, and determining its relationship and category with the standard sample. In this embodiment, the similarity index is a similarity coefficient or a Euclidean distance.
[0047] The spectral data preprocessing step comprises:
[0048] The submicron powder is measured three times, and the sample pool is gently shaken between each measurement to redistribute the sample particles to obtain representative spectral data and reduce the measurement error caused by the local inhomogeneity of the sample particles. During the test, the number of measurements should not be too large to avoid measurement errors caused by charge dissipation;
[0049] After the measurement, the original spectral data collected by the instrument is transferred to the computer and processed using professional spectral analysis software (such as Unscrambler, TQ Analyst, etc.). First, the data of the three measurements are averaged to reduce the impact of random errors.
[0050] The multivariate scattering correction (MSC) method was used to remove the spectral baseline drift and scattering effects caused by differences in sample particle size, shape and surface scattering characteristics. The spectrum was then smoothed using the Savitzky-Golay convolution smoothing algorithm with a window width of 9 points and a polynomial degree of 2 to improve the smoothness and signal-to-noise ratio of the spectrum while retaining the main characteristic information of the spectrum.
[0051] In this embodiment, when the same sample is measured multiple times, due to the electrostatic repulsion between the charged silica particles, the particles are distributed more evenly in the sample pool, thereby improving the repeatability of the measurement results. In multiple measurements, the position deviation of each characteristic absorption peak is within the range of ±2nm. The measured value of the 1100nm absorption peak intensity fluctuates between 1.18-1.22, the 1250nm absorption peak intensity fluctuates between 0.88-0.92, and the 1400nm absorption peak intensity fluctuates between 0.68-0.72, all of which are better than the repeatability when not charged.
[0052] In a specific embodiment, in order to further illustrate the effect of the present invention, the spectrum data is compared with that of uncharged silicon dioxide, and the affinity between saturated charged silicon dioxide, uncharged silicon dioxide and a certain target particle is analyzed.
[0053] like Figure 2 As shown in the figure, when the charging voltage is 5kV, in the near-infrared spectrum range of 900-1700nm, the charged silica particles show characteristic absorption peaks at around 1100nm, 1250nm, and 1400nm. Among them, the absorption peak at 1100nm is related to the first harmonic frequency of the stretching vibration of the Si-O bond in silica; the absorption peak at 1250nm corresponds to the second harmonic frequency of the asymmetric stretching vibration of the Si-O-Si bond; the absorption peak at 1400nm is related to the second harmonic frequency of the symmetric stretching vibration of the Si-O bond. Compared with uncharged silica particles, the intensity of the characteristic absorption peak of the charged silica particles changes due to the presence of charge. Since the charge affects the intermolecular forces and the vibration state of the chemical bonds, the absorption peak intensity is enhanced or weakened.
[0054] like Figure 3As shown in the figure, when the charging voltage is 5kV, the shape of the overall spectrum curve still maintains the typical characteristics of silicon dioxide, but due to the influence of charge, the curve changes in the absorption peak position, and the half-width of the absorption peak increases after charging. When not charged, the half-width of the 1100nm absorption peak is about 50nm, which increases to about 60nm after charging; the half-width of the 1250nm absorption peak increases from about 40nm to about 50nm; the half-width of the 1400nm absorption peak increases from about 35nm to about 45nm. This phenomenon is due to the existence of charge, which changes the electromagnetic field around the particles, affects the interaction between light and particles, and leads to the broadening of the absorption peak.
[0055] In addition, the spectrum curve has a certain drift in the baseline part. Due to the scattering effect caused by the charge, the absorbance value of the baseline in the non-characteristic absorption region such as 900-1000nm and 1500-1700nm increases from about 0.1 when uncharged to about 0.2.
[0056] In a specific embodiment, three kinds of particles are tested, the first kind is a particle without charge injection, the second kind is a particle with saturated charge, and the third kind is a target particle. In the affinity analysis of the three kinds of particles, the absorption peak intensity and the half-height width of the absorption peak are compared, wherein the absorption peak intensity comparison is Figure 4 As shown, the absorption peak position of the saturated charged silica particles is closer to the target particles. The absorption peak intensity of the target particles at 1100nm is 1.1, which is close to the saturated charged silica particles, indicating that there is a certain similarity in the characteristics related to the chemical bond vibration. The absorption peak intensity of the target particles at 1250nm is 0.85, which is slightly different from the saturated charged silica particles. The absorption peak intensity of the target particles at 1400nm is 0.65, which is closer to the saturated charged silica particles.
[0057] The half-height width of the absorption peak of each particle is compared. Figure 5 As shown in the figure, the half-width of the absorption peak of the target particles at 1100nm is about 58nm, the half-width of the absorption peak at 1250nm is about 48nm, and the half-width of the absorption peak at 1400nm is about 42nm, which are closer to the silica particles with saturated charge. In the non-characteristic absorption regions such as 900-1000nm and 1500-1700nm, the baseline absorbance value is about 0.18, which also has a certain drift, and is similar to the baseline drift trend of silica particles with saturated charge.
[0058] In terms of affinity analysis, from the perspective of the position and intensity of the spectral characteristic peaks, the absorption peak intensity of the target particles at 1100nm and 1400nm is relatively close to that of the saturated charged silica particles. There is a certain difference at 1250nm, but there are similarities overall. From the perspective of the half-width of the absorption peak, the half-width of the absorption peak and the baseline drift of the target particles are also related to the saturated charged silica particles, especially the half-width at 1100nm is very close. The results show that the target particles are closer to the saturated charged silica particles than to the uncharged silica particles.
[0059] In addition to the characteristic peak position and intensity, the test results can also be used to analyze the affinity by calculating the similarity coefficient and Euclidean distance. Using the general similarity coefficient and Euclidean distance calculation method, after calculation, the cosine similarity coefficient of the saturated charged silica particles and the target particles is about 0.97, and the Euclidean distance is about 0.12; the cosine similarity coefficient of the uncharged silica particles and the target particles is about 0.90, and the Euclidean distance is about 0.42. This shows that the saturated charged silica particles and the target particles are more similar in terms of the intensity of the spectral characteristic peaks and have a closer affinity.
[0060] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A near infrared spectroscopy test method for charged submicron powders, characterized in that: The steps include: S1, raw material pretreatment step, the submicron powder to be tested is dispersed and then dried; S2, a charge injection step, placing the pretreated submicron powder in an electrostatic generator, setting relevant parameters, and injecting saturated charge into the submicron powder; S3, a spectrum measurement step, placing the submicron powder injected with saturated charge on a test bench to obtain its spectrum; S4, analysis step, preprocessing the spectral data, comparing and matching the preprocessed spectrum with a known submicron powder standard spectrum library, judging the material composition and chemical structure information of the sample by calculating the spectral similarity index, and determining its relationship with the standard sample and category affiliation.
2. The near infrared spectroscopy test method for charged submicron powder according to claim 1, characterized in that: The pre-processing step comprises: Dispersion treatment steps: add a small amount of anhydrous ethanol to the submicron powder and grind it to make the powder evenly dispersed to form a stable suspension; Drying step: The suspension is dried in a vacuum drying oven until the ethanol is completely evaporated.
3. The near infrared spectroscopy test method for charged submicron powder according to claim 1, characterized in that: The relevant parameters include voltage, current and duration.
4. The near infrared spectroscopy test method for charged submicron powder according to claim 1, characterized in that: The spectral data preprocessing step comprises: The submicron powder is measured three times, and the spectral data of the three measurements are averaged; The multivariate scatter correction method is used to remove the spectral baseline drift and scattering effects; The spectra were smoothed using the Savitzky-Golay convolution smoothing algorithm.
5. The near infrared spectroscopy testing method for charged submicron powder according to claim 1, characterized in that: The similarity index is a similarity coefficient or a Euclidean distance.
6. The near infrared spectroscopy testing method for charged submicron powder according to claim 1, characterized in that: The particle size range is 0.1 to 1.0 μm.